Indomethacin can downregulate the levels of inflammatory mediators in the hippocampus of rats submitted to pilocarpine-induced status epilepticus (Clinics, 2014)
OBJECTIVE: Refractory status epilepticus is one of the most life-threatening neurological emergencies and is characterized by high morbidity and mortality. Additionally, the use of anti-inflammatory drugs during this period is very controversial. Thus, this study has been designed to analyze the effect of a low dose of indomethacin (a COX inhibitor) on the expression of inflammatory molecules. METHOD: The hippocampus of rats submitted to pilocarpine-induced long-lasting status epilepticus was analyzed to determine the expression of inflammatory molecules with RT-PCR and immunohistochemistry. RESULTS: Compared with controls, reduced levels of the kinin B2 receptors IL1β and TNFα were found in the hippocampus of rats submitted to long-lasting status epilepticus and treated with indomethacin. CONCLUSIONS: These data show that low doses of indomethacin could be employed to minimize inflammation during long-lasting status epilepticus.